How many jobs are for geologists and are there to many students of geology? - Brenčič, Mihael; Horvat, Aleksander; Verša, Dorotea (Geologija, 1999)
On the contrary with general decrease of interest for natural Science and technology studies, matriculation on the Geology department at University of Ljubljana increases. Despite on the increasing number of students the number of graduates remains more or less constant and ranges between 8 and 15 each year. On the Department of Geology 203 students (10,15 per year) graduated in the last 20 years. At this number of students getting bachelors degrees and already employed geologists 1,35-graduate competite for each job in geology. If eveiy employed geologists would be retired today, it would take 14,7 years to replace them. Mentioned employment parameters are quite comparable with those in USA and do not indicate the prevailing opinion of negative trend. The geological qualification in highest de mand by employers (largest number of job vacancies) in the period between 1993 and 1998 was for graduated geological engineers. The number of unemployed with geological qualification is decreasing while in 1998 there was no unemployed geological engineers. The relationship between demand and supplay for geologist reveals possibilities for employment; for geologists with lower qualification the possibility for employment are lower than for geologists with higher qualification. In 1998 the fill in of job vacancies for geologist was in average 70% (100 % for geological engineers, 80 % for geologists with B.D., 80 % for geologists with M. Sc., 25 % for geologist with Ph.D.). In the USA projections for 2006 the largest decrease of employment will occur in mining and raw materials processing industry (-29,49%). In the governmental agencies and organisations the employment will remain stagnate (+0,08%). In the Services the employment will increase (+27,98). In Slovenia similar trends could be expected. In the mining industry employment stoped. Governmental agencies and organisations already have filled up their needs, however employment in local agencies and organisations still remains possible. Geologists in Slovenia are mainly being employed in research Services and education organisations however the ratio of self-employment and employment in holding and investment offices grows up.